Jump-Diffusion Long-Run Risks Models, Variance Risk Premium, and Volatility Dynamics - Jin, Jianjian (Review of Finance, 2015)
This article calibrates a class of jump-diffusion long-run risks models and quantifies how well they can account for both equity and variance risk premiums while generating realistic volatility dynamics. I find that jumps in the level and the volatility of long-run consumption growth rates perform equally well in explaining the variance risk premium. Moreover, compared to jump-in-growth models, jump-in-volatility models generate more realistic volatility dynamics and stronger predictability of returns by the variance risk premium. Finally, both jump-in-volatility and jump-in-growth models suggest that a nontrivial portion of the equity risk premium is due to compensation for jump risks.